Pengaruh Fraud Diamond Theory sebagai Uji Identifikasi terhadap Fraudulent Financial Statement : Studi Empiris pada Perusahaan Property dan Real Estase yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Indah Fitrianjani; Martini Martini (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine how the Diamond Fraud theory impacts indications of fraudulent financial statements in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. According to the Diamond Fraud theory, there are four main components that drive financial statement fraud: pressure, opportunity, rationalization, and capability. In this study, pressure is measured through financial targets, opportunities are measured through supervisory performance, and rationalization is measured through auditor turnover. Financial statement errors are considered a significant issue because they can reduce the quality of accounting information, which impacts stakeholders making business decisions. Using a purposive sampling method, the study sample consisted of 49 companies, resulting in a total of 245 observations. SPSS 22 was used to conduct logistic regression on the data. The results show that financial targets and director turnover do not affect the potential for fraud. Conversely, auditor turnover and ineffective supervision increase the likelihood of financial statement fraud. These results contribute to the academic literature on forensic accounting and provide empirical evidence on the relevance of the Diamond Fraud theory in Indonesia. From a practical perspective, this research emphasizes the importance of sound auditor oversight and independence in preventing and detecting fraudulent practices. This can increase investor, creditor, and other stakeholder confidence in the quality of financial reporting.